Blockchain-based Intrusion Detection System of IoT urban data with device authentication against DDoS attacks. (October 2022) - Babu, Erukala Suresh; BKN, SrinivasaRao; Nayak, Soumya Ranjan; Verma, Amit; Alqahtani, Fayez; Tolba, Amr; Mukherjee, Amrit
Highlights: To model the arbiter PUF that secures the keys pairs using lightweight technology. Authenticate the IoT devices using blockchain system. Propose a collaborative anomaly detection system against DDOS Attacks on IoT devices with blockchain. Abstract: The Internet of Things (IoT) is a technology enabler for enhancing the urban physical infrastructure and providing public services. However, public access to collected heterogeneous IoT urban data is more vulnerable to hackers invading intellectual property as all devices are connected to the internet. IoT security plays a vital role in the smart city. This IoT security is a real challenge as multiple goals and major inconveniences slow the rapid adaption of these smart devices. This paper presents a permissioned-based blockchain system that uses the arbiter PUF model to secure the key pairs of IoT devices using lightweight technology. A collaborative detection system is initially used to detect the DDoS on IoT devices using the machine learning-based ensemble technique, which provides a lower false-positive rate and better detection rate than the other classification technique. Next, we incorporated the blockchain system that securely shares the alarm alerts to all the nodes of the IoT network with adequately secured authentication. Graphical abstract: Image, graphical abstract